2012
DOI: 10.1111/j.1752-0606.2011.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Social Class: Voices of Inter‐Class Couples

Abstract: Social class is not often discussed or examined in-depth in couple and family therapy research and literature even though social class shapes familial relationships and is considered an important variable in marital satisfaction. In this qualitative study, we explored the perceptions of eight couples who made lasting commitments across class lines by asking them about the impact of their social class backgrounds on their relationships. Three categories of themes emerged including: (a) differences and similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Unfortunately, while social class is an important contextual variable for individuals and families, it is a relatively neglected topic in the mental-health literature (McDowell et al, 2013). Even so, several psychological constructs can aid in our understanding of the feelings of inferiority, resentment, and envy felt toward wealthier individuals.…”
Section: Rich People Are Greedy and Money Corruptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, while social class is an important contextual variable for individuals and families, it is a relatively neglected topic in the mental-health literature (McDowell et al, 2013). Even so, several psychological constructs can aid in our understanding of the feelings of inferiority, resentment, and envy felt toward wealthier individuals.…”
Section: Rich People Are Greedy and Money Corruptsmentioning
confidence: 99%
“…For example, researchers from the University of California-Berkeley observed that, because of more access to material resources and a higher social rank, wealthy people have less compassion for the suffering of others than do those in lower socioeconomic classes (Stellar, Manzo, Kraus, & Keltner, 2012). Researchers have documented incidences in which individuals from upper-class families are uncomfortable identifying themselves as such and try to distance themselves from those with a similar socioeconomic status (SES) because of negative stereotypes of upper-class privilege (McDowell et al, 2013). However, it is uncertain the extent to which negative stereotypes of the wealthy are the result of consistent patterns of negative behaviors on the part of the wealthy or psychological factors of those who hold them in ill-regard.…”
mentioning
confidence: 99%
“…SES is noted as one's hierarchical economic position in which the lower strata is often associated with greater health risks. Social class is defined as economic (income and other material resources), social (people that can be relied on for access to resources), and cultural (beliefs and ways of living that provide additional access to social and economic resources) capital (McDowell et al, 2013). Social class incorporates a number of other factors that are not assessed when measuring SES.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…With this in mind, I am happy to see recent articles related to the treatment of the homeless (Harris‐McKoy, Woods, Brantley, & Farineau, ; Holtrop, McNeil, & McWey, ), those with physical and mental health issues (e.g., Houston‐Barrett & Wilson, ; MacPherson, Leffler, & Fristad, ; Wagner et al., ), those marginalized because of their sexual orientation, race, or other reasons (e.g., Coolhart, Baker, Farmer, Malaney, & Shipman, ; LaSala, ; Maciel & Knudson‐Martin, ; Quirk, Strokoff, Owen, France, & Bergen, ), those at risk for relational violence (Salis, Kliem, & O'Leary, ; Schneider & Brimhall, ; Taylor & Borduin, ), and substance abuse (e.g., Ladd & McCrady, ; Soloski, Kale Monk, & Durtschi, ). Similarly, we continue to publish important articles related to gender, power, culture, class, and their intersection (e.g., Knudson‐Martin et al., ; McDowell, Brown, Cullen, & Duyn, ; McDowell, Melendez‐Rhodes et al., ; Seedall, Holtrop, & Parra‐Cardona, ; Seshadri & Knudson‐Martin, ; Van Parys & Rober, ; Williams, Galick, Knudson‐Martin, & Huenergardt, ; Williams & Knudson‐Martin, ).…”
mentioning
confidence: 99%